Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Belanja Modal terhadap Kinerja Keuangan Pemerintahan Kabupaten/Kota di Provinsi Bali Tahun 2018 – 2021 - Dafillah Vike Eryana; Dwi Fera Istiqomah; Olivia Anandyta; Zida Rizqi Amalia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Capital Expenditure on the financial performance of district / city governments in Bali Province in 2018-2021. The method used is multiple linear regression analysis with a quantitative approach, using secondary data obtained from the realization report of the Regional Budget (APBD). The results showed that partially only PAD had a significant effect on regional financial performance, while DAU and Capital Expenditure had no significant effect. But simultaneously, the three variables together have a significant effect on the financial performance of local governments.